Educational Management of Educational Institutions In Limitation’s State: Case Studies: Junior High School-Based Pesantren Child’s Of Indonesian Migrant Workers "Mutiara Bangsa" In Sebatik Of Nunukan District (International Journal of Scientific Research and Management (IJSRM), 2018)
Junior High School Based Pesantren (SMPBP) Mutiara Bangsa is an implementation of community-based management model developed by the government as one alternative in dealing with border education issues, both educational issues due to the characteristics of the border areas themselves, as well as problems related to the education of child’s Indonesian Migrant Workers (TKI) who have not met national education policy expectations and MDGs commitments. The focus of this study is the management of integrated educational management of public education units with religious education units; the educational role of existing an educational institution in Sebatik Nunukan North Kalimantan, as a community-based educational institution that supports government programs and helps tackle educational issues in border areas. This study uses the Case Study method, through data collection through participatory observation, in-depth interviews, and documentation and data analysis as used by K. Yin. Research result titled Educational Management of Educational Institutions in Border Areas, Case Study at Junior High School- Based Pesantren Mutiara Bangsa Sebatik Nunukan District. First, Mutiara Bangsa education institution is the right alternative in the border area to fulfill the hope of increasing human resources of society, the form of strategic government policy, and indirectly maintain the integrity of Indonesian workforce. Second; the nation’s education institution implements the function of planning, organizing, actuating and controlling as well as in other educational units, but there are differences in the handling of the child of Indonesian Migrant Workers, Third, the Mutiara Bangsa’s education institution has a strategic role in the border area as a container of government program implementation, National defense; realizing character education, providing educational services in 3T areas and an alternative education for Childs Indonesian Migrant Workers